Benthic foraminiferal assemblages and environmental drivers along the Kveithola Trough (NW Barents Sea) - Caridi, Francesca; Sabbatini, Anna; Bensi, Manuel; Kovačević, Vedrana; Lucchi, Renata Giulia; Morigi, Caterina; Povea, Patricia; Negri, Alessandra (Journal of Marine Systems, 2021)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. We describe the population density, biodiversity and vertical distribution in the sediment of benthic foraminifera, and their relationship to environmental parameters, in the Kveithola Trough (NW Barents Sea). Two staining methods, Cell Tracker Green (CTG) and Rose Bengal (RB), were used to distinguish between living and dead tests. CTG proved to be more effective than RB, and we therefore used this approach to document faunal assemblage variability along a transect of the Trough. The outer shelf shows a diverse benthic foraminiferal assemblage suggesting an oxygenated and oligotrophic environment. The central part appears to be a disturbed area due to rapid circulation changes and organic matter burial in sediments where opportunistic foraminifera colonize only the first centimetres. In contrast, the inner part of the Trough seems to be a stressed environment where species associated with organic-rich sediment and oxygen-depleted environments dominate the living assemblage. At all sites, delicate monothalamids species form part of the assemblage. The peculiar geomorphological and environmental conditions of this area, and the high regional primary and secondary production, are key drivers of foraminiferal assemblage distribution